RELATIONS OF THE MAMLUK SULTANATE WITH THE ITALIAN STATES (BASED ON ITALIAN SOURCES) (Journal of history, 2024)
In the Middle Ages, the Mamluk Sultanate was one of the main medieval Muslim states in the East. From the moment the Mamluk Sultanate was established, it began to maintain contacts with foreign countries in various fields. During its existence, the Mamluks established relations with European states, including the Italian republics. In the 13th-16th centuries, the relations established with the Italian states became a branch of the international relations system in Europe at that time. The scientific article examines the history of political relations between the Mamluk Sultanate and the Italian states. A scientific analysis of diplomatic relations that developed on the basis of trade relations between the Italian republics and the Mamluk Sultanate is carried out. Diplomatic and political relations between the Italians and the Mamluks are assessed as a direction of medieval diplomacy. Based on Italian materials, the history of relations between the Venetian, Florentine and other Italian republics, which were interconnected by diplomatic and international relations, with the Mamluk Sultanate is presented. At the same time, the political position of the Mamluks in relation to the Italians and the main directions of foreign relations are considered.
Keywords: Mamluk Sultanate, Italian states, trade, embassy, political relations, Italian materials.